A Rare Cause of ST-Segment Elevation Myocardial Infarction in COVID-19: MINOCA Syndrome - Eroglu, Serkan Emre (Medeni Med J, 2021)
Myocardial infarction with nonobstructive coronary arteries (MINOCA) is defined as having a stenosis of less than 50% or no stenosis in coronary angiography in a patient diagnosed with myocardial infarction. Because of its thrombogenic predisposition in COVID-19, the diagnosis of MINOCA syndrome is rarely thought in the patients with ST-segment elevation myocardial Infarction on electrocardiogram. In this case report, we discuss a 47-year-old male patient diagnosed with MINOCA who was followed up with respiratory failure due to COVID-19 viral pneumonia in intensive care unit. His 12-lead electrocardiogram showed “inferior STEMI”. A 30-40% stenosis was also shown in the midportion of left anterior descending artery in emergency coronary angiography. The patient had a normal computed tomographic pulmonary angiography and was discharged with a full recovery. MINOCA may be triggered by hyperinflammation or various processes due to COVID-19. To explain these processes associated with MINOCA syndrome, further clinical trials are needed.